Who Benefits from the Past? The Process of Cultural Heritage Management in the Field of Animation in Poland (The Case of the Se-Ma-For Film Studio in Łódź). (July 2019) - Ciszewska, Ewa
With a view to studying the social and institutional practices related to the post-1989 approaches to film animation under socialism, this article addresses the transformation of the state-owned Se-Ma-For Film Studio in Łódź and the private company that later took over its name (the Se-Ma-For Film Company). The chronological scope of the study extends from 1989 to 2016; however, to identify the impact of the 1989 watershed on the animation market in Poland, modalities of operation of animation film studios in state-socialism era are presented. This article addresses the question of which heritage communities work with the memory of the animated film studio in Łódź, as well as the issue of the ways in which cultural heritage management processes have taken place. The article makes the case that the approving attitude towards the organizational and aesthetic values of Poland's film industry under socialism has become a characteristic feature of strategies leading to the cultural heritage management of Polish film animation from this period. In conclusion, the author asserts that the commercialization of the cultural heritage of the former state-owned studio benefited the economic and symbolic capital of two institutions, the Museum of Cinema and the Se-Ma-For Film Company, as well as the city of Łódź, which branded itself as a city of film.